Efetividade dos direitos fundamentais laborais: abertura do sistema jurídico por meio da jurisprudência (do positivismo ao pós-positivismo) - Carneiro Filho, Roberto (2016)
Dynamism and hypercomplexity as inherent characteristics of social relations molded to the concepts and values prevailing in the twenty-one century require of labor law scholar the permanent exercise of intellectual activity through critical reflections on the legal system currently existing labor regulations. In this sense, the present doctoral thesis, through theoretical and jurisprudential analysis, defends the transformation of labor law application method, to overcome the legal positivism and building a labor law post-positivist, for the purpose of seeking the application of labor law in order to bring it closer to the social reality, as well as it can give effect to labor fundamental rights with the constitutionalization of private law, which only shows possible since the use of legal interpretation mechanisms that are more open and flexible, supported the theory of legal argument. So this thesis PhD proposes that the labor courts in Brazil be the protagonist in the implementation of norms and constitutional values, giving effectiveness on labor fundamental rights, it may avail themselves of the general terms and undefined legal concepts like open windows through which it shows possible constitutionalising private law, observing always the balance between explicit and implicit constitutional values. Therefore, the case law as a source of labor law, against the legislative lethargy, it should take advantage of the constitutional activism to build the rule of law from case, as it did the Venerable Superior Labor Court when editing some statements of jurisprudence: item III of P. 244, item III of P. 378, P. 440 and P. 443